2021
DOI: 10.1088/1361-6501/ac0b16
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Assessment on Long-Term Performance of BDS-2/BDS-3 Satellite Atomic Clocks

Abstract: Recently, the performance of the new-generation BeiDou Navigation Satellite System (BDS) satellite clocks has attracted considerable attention. There are two types of BDS clocks developed in China—namely, the new rubidium (Rb-II) and passive hydrogen maser (PHM)—and these can affect positioning, navigation and timing (PNT) services. In this paper, to comprehensively evaluate and analyze the performance of BDS satellite atomic clocks, the physical characteristics are exhibited, including phase, frequency, frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The OADEVs are 4.03×10 14 , 2.24×10 14 , and 0.22×10 14 1000 s, 10,000 s, and 1 day, respectively. • BDS-3 MEO Rb: It can be seen that the stability of MEO Rb clocks is slightly w than that of BDS-3 MEO PHMs, with the OADEVs being 4.3×10 2.56×10 14 , and 0.25×10 14 s/s at 1000 s, 10,000 s, and 1 day, respectively. The bottom two plots in Figure 10 depict the OADEVs for PHMs on IGSO and GEO satellites.…”
Section: Frequency Stability Analysismentioning
confidence: 95%
See 3 more Smart Citations
“…The OADEVs are 4.03×10 14 , 2.24×10 14 , and 0.22×10 14 1000 s, 10,000 s, and 1 day, respectively. • BDS-3 MEO Rb: It can be seen that the stability of MEO Rb clocks is slightly w than that of BDS-3 MEO PHMs, with the OADEVs being 4.3×10 2.56×10 14 , and 0.25×10 14 s/s at 1000 s, 10,000 s, and 1 day, respectively. The bottom two plots in Figure 10 depict the OADEVs for PHMs on IGSO and GEO satellites.…”
Section: Frequency Stability Analysismentioning
confidence: 95%
“…Moreover, the 2-hour, 10-hour, and 7-day prediction precisions of BDS-3 PHMs are about 0.3, 0.4, and 2.2 ns, respectively [16]. The daily stability of BDS-3 MEO satellites is about 2-5 × 10 −15 s/s [14]. The stability level of the BDS-3 PHMs is comparable to that of the PHMs of the Galileo as well as to the Rb clocks of the GPS Block IIF; meanwhile, the improved BDS-3 Rb clock is comparable to that of the Galileo Rb clock [17].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Orbit determination based on inter-satellite links (ISLs) was studied by several authors (Wang et al, 2019;Ruan et al, 2020;Guo et al, 2020;Xie et al, 2020) but none of the MGEX ACs uses ISL data due to lack of public availability. Chen et al (2021) found that the clock stability of the BDS-3 satellites is improved compared to BDS-2 but also shows periodicities at the orbital frequencies. Cao et al (2021) confirm the improved quality of the observed BDS-3 clocks although the Galileo clocks slightly outperform them.…”
Section: Introductionmentioning
confidence: 96%